2017
DOI: 10.1186/s12936-017-1697-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of Plasmodium falciparum specific naïve, atypical, memory and plasma B cells during infancy and in adults in an endemic area

Abstract: BackgroundB-cells are essential in immunity against malaria, but which sub-sets of B-cells specifically recognize Plasmodium falciparum and when they appear is still largely unknown.ResultsUsing the flow cytometry technique for detection of P. falciparum specific (Pf+) B-cells, this study for the first time measured the development of Pf+ B cell (CD19+) phenotypes in Ugandan babies from birth up to nine months, and in their mothers. The babies showed increases in Pf+ IgG memory B-cells (MBCs), atypical MBCs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 80 publications
0
33
0
Order By: Relevance
“…Consistent with the observation of febrile malaria children in Mali, malaria induces the activation of Th1 cytokines and Tfh-1 cells that contribute to the expansion of T-bet hi atypical MBCs, also causing reduced BCR signaling 25 . The study of development of MBCs in newborns and mother in malaria endemic area in Uganda showed an expansion of atypical MBCs and non-IgG + MBCs which increased with age 26 . In a low malaria transmission area in Brazil, found that single- and multiple- P .…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with the observation of febrile malaria children in Mali, malaria induces the activation of Th1 cytokines and Tfh-1 cells that contribute to the expansion of T-bet hi atypical MBCs, also causing reduced BCR signaling 25 . The study of development of MBCs in newborns and mother in malaria endemic area in Uganda showed an expansion of atypical MBCs and non-IgG + MBCs which increased with age 26 . In a low malaria transmission area in Brazil, found that single- and multiple- P .…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the CMV+ group was defined by high titers of cord blood CMV IgM rather than the gold standard of neonatal CMV Ag or PCR detection in urine which was not feasible at the time of the study. We did not examine infectious disease Ag-specific MBC such as Pf-specific MBC which have been performed by Lugaajju et al and show Pf-specific MBC in various subsets (110). Also, inclusion of the two neonates with congenital CMV and exposed to HIV into the HIV exposed group could have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…Several observations suggest that P. falciparum infection per se drives the expansion of aMBCs including a positive correlation between aMBC expansion and intensity of P. falciparum transmission in studies primarily carried out in Africa including Mali (25, 26, 32), Uganda (28, 33, 34), Kenya (35, 36), the Gambia (37) and Ghana (38). Of interest, in HIV-malaria coinfected Rwandan adults the expansion of aMBC was greater as compared to that in individuals infected with malaria alone (39).…”
Section: Introductionmentioning
confidence: 99%